Oxidative DNA damage: mechanisms, repair and disease - Dizdaroglu, Miral (Henry Stewart Talks, 2007)
Formation of reactive oxygen species, Oxidative damage to DNA bases by free radicals, Techniques used for the measurement of DNA damage and repair, Biological responses to genomic DNA damage, Mechanisms of base-excision repair, Determination of substrate specificities of DNA glycosylases in-vitro and in-vivo, Mouse and human NEIL1 proteins, Cockayne syndrome, CSB protein
Archived at 2018/12/10